Staying on the ball during COVID-19 pandemic: impact on training modalities in football players - Schüttler, D.; Hamm, W.; Krammer, S.; Steffen, J.; Deuster, E.; Lauseker, M.; Egger, F.; Meyer, T.; Brunner, S. (The Journal of Sports Medicine and Physical Fitness, 2022)
Background COVID-19 pandemic has affected worldwide sports competitions and training in both amateur and professional leagues. We thus aimed to investigate changes in different training modalities in elite and amateur football players following COVID-19 lockdown in March 2020. Methods In this cross-sectional study we applied a Likert scale-based questionnaire with 20 items to quantify and classify time spent at standard training methods in 47 professional and 54 amateur football players from 12 Austrian clubs before and during lockdown. Additionally, McLean score was calculated to assess perceived training fatigue. Results Weekly amount of training time at endurance exercises (cycling) increased in both professional (37.5 [IQR 46.5] min/week vs. 187.5 [IQR 127.5] min/week, p<0.001), and amateur players (0.0 [IQR 45.0] min/week vs. 37.5 [IQR 112.5] min/week, p=0.015) during COVID-19 lockdown. Time on diverse muscle strengthening workouts was significantly elevated in both cohorts. Total training time at ball declined for professionals (from 472.5 [IQR 150] min/week to 15.0 [IQR 112.5] min/week, p<0.001) and amateurs (from 337.5 [IQR 285] min/week to 0.0 [IQR 37.5] min/week, p<0.001). Videoguided training was intensified in both groups (p<0.001 each). Location shifted from football fields and gyms to home and outdoors. Overall McLean score remained unchanged in amateurs (p=0.42) while elite players showed a trend towards an increase (p=0.056). Conclusions COVID-19 lockdown compromised football training, especially training concepts with ball. Consequently, resulting changes in exercise loads and muscular burden might impact susceptibility for injuries and impair performances especially in amateur players, especially as they lacked training supervision and professional training plans. Minimum effective dose of training workload in order to maintain endurance- and neuromuscular-related performance parameters should be prescribed.